Perencanaan Sistem Pemanenan Air Hujan (Rainwater Harvesting) di Masjid Al Mu’minin Kota Kendari - Rizky, Septina; Ilham, Ilham; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
The need for clean water in mosques, especially for ablution water needs, is something that needs to be addressed. Lack of clean water during the dry season can be a problem for some mosques, such as the Al-Mu'minin mosque which experiences a shortage of groundwater volume during the dry season and groundwater becomes a little smelly. This study aims to determine the potential of rainwater through hydrological analysis and can plan a rainwater harvesting system at the Al-Mu'minin mosque. The results obtained are the amount of water needed for ablution at the Al-Mu'minin mosque is as much as 6.97 m3/day or equivalent to 209.11 m3/month. This result is obtained from the calculation of the number of worshipers per day with the need for ablution water per prayer time, which is 4.42 liters/person. Next, a hydrological analysis was calculated and the result was 45.51 mm/hour of rain intensity, which was then used to calculate the volume of rainwater that could be accommodated so that the result was 7.81 m3/day or equivalent to 234.3 m3/month. Based on the calculation results, the piping system used is 4 inches for horizontal pipes and 3 inches for standpipes.